Arquitetura, Cidade e Modenidade: a obra do engenheiro Cícero Ferraz em Teresina, Piauí (1930 - 1950) - Figueiredo, Camila Soares de (2023)
This research aims to investigate the relationship between the context of modernization in the city of Teresina, Piauí, and the transformations identified in architecture and in the city, emphasizing the work of engineer Cícero Ferraz de Sousa Martins, between the 1930s and 1950s, as an important agent in this process. The perspective of modernization has always been a principle linked to the history of Teresina, since Teresina was established in the 19th century with the task of adapting to the ideals of desired progress, and boosting the development of the province, which was not being achieved by the then capital. Oeiras. Over the decades and the arrival of a new century, the search for modernity became constant and economic activities were essential to promote the intended transformations. In that regard, there are associations between economic cycles of development and changes in urban and architectural culture, concomitantly, in each phase, with the contribution of engineering professionals who worked in the construction of the capital. Within this scenario, the productions of engineers such as Cícero Ferraz stand out, who gained notoriety in a period of intense modernization in the capital, whose collection, built between 1930 and 1950, is representative for the understanding of the sociospatial dynamics verified in Teresina. It has a remarkable set of residential works, however, it stands out especially for its institutional production, since they are examples that translate the spirit of modernity, expressing and reproducing the intentions and context in which they were built. As for the methodology employed, the theoretical assumptions of the research are based on the framework built from bibliographical reviews regarding the subject under study. With regard to practical assumptions, it comprises surveys of primary and secondary sources in physical and virtual repositories, with emphasis on collections of photographs, maps and drawings, in addition to visits to the analyzed buildings, oral reports and redesign practices. In this way, the work addresses the theme of modernization and the arrival of engineers until the performance of Cícero Ferraz in Teresina, to then analyze the works chosen from the criteria that could encompass all the plurality and its attributes of architectural modernity. Therefore, such analyzes are based on the idea of the “Contemporary Quaternary”, by Edson Mahfuz, which involves place, program, construction and formal structures. Therefore, the work collaborates for the rescue of the memory of the work of Cícero Ferraz and recognition of his contribution as an engineer to architecture and to the city, also highlighting his role as an important agent of modernization, from the documentation, appreciation and stimulus to conservation of their works.